Relasi ilmu sejarah dengan ilmu sosial dan relevansinya di Lembaga Madrasah - Susilaweti, Susilaweti (ARKA INSTITUTE, 2022)
Various kinds of social problems during the colonial era that arose became a challenge for madrasah to continue to maintain its existence until now. The purpose of this study is to analyze the relationship between history and social science and its relevance in Madrasah Institutions. The approach used in this study is a literature approach. The literature approach includes the use of literature sources such as books, scientific articles, documents, and other references as the foundation of this research. This research will lead to the exploration and analysis of literature sources related to the relationship between History and Social Sciences, as well as their relevance in the context of madrasah institutions. The results show that history and social sciences have a relationship in human development from each era. By socializing humans will be able to print their own history. Then madrassas are qualified for historical value or history that can be formed and created because of the empathy and sympathy of the archipelago's scholars for Islamic education in the form of madrassas that have closeness and direct contact with the lower middle class.